BPJS Membership as The Terms for The Transfer of Land Rights Registration Due to Sale and Purchase by a Limited Company - Choirunnisa Aprilita Andan; Fransiscus Xaverius Arsin (IHSA Institute, 2022)
Land rights can be granted to individual legal subjects (natuurlijk person) and legal entities (Recht person). BPJS membership as a term for the transfer of land rights registration due to sale and purchase made by Limited Company after the issuance of Presidential Instruction (Inpres) Number 1 of 2020 about the Optimization of Jaminan Kesehatan Nasional (known as JKN, the national health insurance) Implementation. The focus of this research is the implementation of the BPJS membership requirement for transfer of land rights registration due to sale and purchase that is applied for Limited Company. The method used in this research is juridical normative and literature reviews on relevant legal literature. The result of this research shows that BPJS membership is also applied as the terms for Limited Company as the purchaser. The required BPJS membership attached is owned by the member of the Limited Company who is appointed as the representative of the Limited Company.